Indonesia's Downstream Diplomacy Strategy Through BRICS Membership - Larasati Larasati; Elyana Ade Pertiwi (Laboratorium Hubungan Internasional, FISIP, Universitas Jenderal Soedirman, 2026)
Abstract As an effort to increase economic independence and export value, strategic natural resource hilirisasi diplomacy is a top priority for Indonesia. Indonesia's membership in BRICS in 2025 will open-up opportunities for the country to design a roadmap for advanced commercial diplomacy and utilize this forum to increase market diversification, attract investment, and foster technological collaboration. This article examines Indonesia's steps in developing a long-term diplomatic plan through BRICS while upholding the principle of an